THE INFLUENCE OF LEARNING MODEL TYPE OF JIGSAW AND LITERACY ABILITY TO STUDENT’S ACHIEVEMENT OF CIVICS IN 5TH GRADE OF PRIMARY SCHOOL 040443 KABANJAHE FOR YEAR ACADEMIC 2020/2021 - Gabriela Anjelika Br Sebayang; Reh Bungana Br. Perangin-angin; Zulkifli Matondang (Sensei International Journal of Education and Linguistic, 2021)
This study aims to determine the effect of the use of cooperative learning model Jigsaw and literacy ability on students learning outcomes on the material of right, obligations and responsibilities in the 5th grade of primary school 04043 Kabanjahe for year academic 2020/2021. The type of this research is quasi experiment with 2 x 2 factorial design. The population of this research is all the fifth grade students of primary school 04043 Kabanjahe with total population 60 students. The selection of sample is conducted by total sampling technique that is from two existing classess as a whole as sample. Thus, the sample is devide into two classes of VA and VB. The determination of the class for implementation of the learning model was determined by class VA that consisted of 30 students for class which are taught with conventional learning model, while the VB was taught with Jigsaw type learning model. The instrument of this study were using multiple choice with total 30 questions. The instrument of literal ability was in the form of essay with total questions 15 items. All of instruments were valid and reliable. The data of this research were analyzed by t test. The result showed that the learning outcomes of Civic learer who were taught using model of jigsaw learning gain the higher score than the conventional one. The result of learning Civics of students who have a positive literacy ability is higher than the learning outcomes of students who have a negatif literacy ability. There is the effect of different learning model on learning outcomes.